Different Responses of Various Chlorophyll Meters to Increasing Nitrogen Supply in Sweet Pepper - Padilla, Francisco M.; de Souza, Romina; Peña-Fleitas, M. Teresa; Gallardo, Marisa; Giménez, Carmen; Thompson, Rodney B. (Frontiers in Plant Science, 2018)
Intensive vegetable production is commonly associated with excessive nitrogen (N) fertilization and associated environmental problems. Monitoring of crop N status can enhance crop N management. Chlorophyll meters (CMs) could be used to monitor crop N status because leaf chlorophyll (chl) content is strongly related to crop N status. To monitor crop N status, relationships between CM measurements and leaf chl content require evaluation, particularly when excessive N is supplied. The SPAD-502 meter, atLEAF+ sensor, MC-100 Chlorophyll Concentration Meter, and Multiplex sensor were evaluated in sweet pepper with different N supply, throughout the crop, ranging from very deficient to very excessive. CM measurements of all sensors and indices were strongly and positively related to leaf chlorophyll a + b content with curvilinear relationships over the entire range of chl measured (approximately 0–80 μg cm-2). Measurements with the SPAD-502, and atLEAF+, and of the Multiplex’s Simple Fluorescence Ratio index (SFR) had asymptotic responses to increasing leaf chl. In contrast, the MC-100’s Chlorophyll Content Index (CCI) had a progressively increasing response. At higher chlorophyll a + b contents (e.g. >40 μg cm-2), SPAD-502, atLEAF+ and SFR measurements tended to saturate, which did not occur with CCI. Leaf chl content was most accurately estimated by CCI (R2=0.87), followed by the SPAD-502 meter (R2=0.85). The atLEAF+ sensor was the least accurate (R2=0.76). For leaf chl estimation, CCI measured with the MC-100 meter was the most effective of the four sensors examined because it: (1) most accurately estimated leaf chl content, and (2) had no saturation response at higher leaf chl content. For non-saturating leaf chl content (approximately 0–40 μg cm-2), all indices were sensitive indicators. As excessive applications of N are frequent in intensive vegetable crop production, the capacity of measuring high leaf chl contents without a saturation response is an important consideration for the practical use of chlorophyll meters.